Deformation analysis of reinforced earth wall subjected to applied loads - Sia, Ee Hou (2009)
Reinforced Earth (RE) wall has been used widely in Malaysia. However, not much study has been implemented on the deformation of RE Wall subjected to various applied loads. This study focuses on the behavior of original Reinforced Earth wall where high friction reinforcing strips are used as soil reinforcement. Finite element models are used to simulate the response of the RE Wall under the various type of applied loads. Field instrumentations are used to measure the actual deformation of RE wall on site. The field lateral movements of RE wall at facing panels under the applied loads are compared with the analysis result. From the results, the suitability of the soil models for RE wall modeling can be pre-determined. Parametric study are performed on the response finite element models with various RE strip length over wall height ratios (L/H) subjected to traffic loads, bridge loads and horizontal loads due to compaction force. Based on series of parametric studies, correlation between L/H ratios subjected to various loads can be obtained and location of maximum lateral deformation at the wall facing can be pre-determined. Besides that, finite element analysis was performed on the RE wall with trapezoidal approach subjected to traffic live load. Saving on strip length based on trapezoidal approach without jeopardizing the wall deformation are discussed.